Depression, hormonal status and erectile dysfunction in the aging male: results from a community study in Malaysia - Low, W.Y.; Khoo, Ee Ming; Tan, H.M.; Hew, F.L.; Teoh, S.H. (Elsevier, 2006)
Background: Depression and erectile dysfunction (ED) are common in aging and the two conditions often co-exist. These conditions have been shown to be associated with hormonal changes in men. This paper examines the association between depression, ED, and hormonal status of men aged above 50 years in the Klang Valley, Malaysia. Methods: Five hundred men aged 50 years and above were randomly selected via the electoral roll and invited to participate in a community-based study on men's health: 351 men responded. Respondents were interviewed individually based on a self-developed questionnaire, which included information on socio-demographic data. Erectile function was measured using the International Index for Erectile Function-5 (IIEF-5) and depression was measured using the 15 item Geriatric Depression Scale (GDS-15). Results: Sixty-nine percent of the men were diagnosed with ED. Mean GDS score was 3.33 (SD = 3.29). Nineteen percent (n = 67) of the men had abnormal levels of testosterone (â¤11 nmol/l) and this comprised 73 of men with ED (n = 49) and 27 of men without ED (n = 18). There was no significant association between testosterone level and ED (Ï2 = 0.68, p = 0.41). Significant association was found between depression (GDS â¥ 5) and men with ED (Ï2 = 6.07, p = 0.014). Sex hormone binding globulin and luteinising hormone were negatively correlated with erectile function. Results of the multiple linear regression showed that age and depression are predictors of erectile function. Conclusion: Depression and ED should be screened for when either exists in the male patient and treatment directed accordingly. Â© 2006 WPMH GmbH.